Socio-economic and geographic profiling of crime in Chile - Mauro Gutiérrez; Javier Núñez; Jorge Rivera (CEPAL Review, 2009)
Many empirical studies of crime assume that victims and perpetrators live in a single geographical unit, the implication being that the socio-economic characteristics of victims’ places of residence can be treated as determinants of crime. This study offers an alternative approach which consists in measuring crime by the proportion of alleged offenders in the whole population and treating the characteristics of their home communes as socio-economic causes of criminal behaviour. The conclusion is that those charged with crimes present a high degree of geographic mobility. In the case of economically motivated crimes, the evidence partly supports Becker’s propositions. Lastly, we show that the number of people charged with crimes tends to be greater in communes that have low incomes, a larger police presence, a predominance of urban areas with higher levels of education and a geographical location in the north of the country, which to some degree bears out the findings of other studies on Chile.